Healthcare As a Universal Human Right : Sustainability in Global Health. - Nunes, Rui. (Milton : Taylor & Francis Group, 2022)
This important book outlines how, despite varying levels of global socio-economic development, governments around the world can guarantee their citizens' fundamental right to basic healthcare.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books